2005
DOI: 10.5194/nhess-5-63-2005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ULF magnetic anomaly during Izu earthquake swarm and Miyakejima volcano eruption at summer 2000, Japan

Abstract: Part of Special Issue "Precursory phenomena, seismic hazard evaluation and seismo-tectonic electromagnetic effects" Abstract. Results of the ULF electromagnetic emission during the Izu, 2000 earthquake (EQ) swarm and Miyake volcano eruptions during the summer period of 2000 are presented and analyzed. The analysis of the obtained data has been performed in 3 main directions: traditional statistical analysis, i.e. analysis of time dynamics of spectral density, polarization ratios and their derivatives, Principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…So far, there have been many reports on the ULF electromagnetic phenomena associated with the 2000 Izu Islands earthquake swarm. Different kinds of methodologies have been performed, such as principal component analysis (PCA) (Uyeda et al, 2002;Hattori et al, 2004b), fractal analysis (Gotoh et al, 2004;Telesca et al, 2007Telesca et al, , 2008, polarization analysis (Ismaguilov et al, 2001(Ismaguilov et al, , 2003Kotsarenko et al, 2005) and direction-finding analysis (Ismaguilov et al, 2003;Kopytenko et al, 2006). In previous studies, the most significant results were found in H (N-S) component by PCA and fractal analysis.…”
Section: Introductionmentioning
confidence: 90%
“…So far, there have been many reports on the ULF electromagnetic phenomena associated with the 2000 Izu Islands earthquake swarm. Different kinds of methodologies have been performed, such as principal component analysis (PCA) (Uyeda et al, 2002;Hattori et al, 2004b), fractal analysis (Gotoh et al, 2004;Telesca et al, 2007Telesca et al, , 2008, polarization analysis (Ismaguilov et al, 2001(Ismaguilov et al, , 2003Kotsarenko et al, 2005) and direction-finding analysis (Ismaguilov et al, 2003;Kopytenko et al, 2006). In previous studies, the most significant results were found in H (N-S) component by PCA and fractal analysis.…”
Section: Introductionmentioning
confidence: 90%
“…Different methods of analysis have been developed: polarization analysis by means of the ratio of vertical magnetic field component to the horizontal (Hayakawa et al, 1996), fractal analysis (mono-and multi-) (Hayakawa et al, 1999;Smirnova et al, 2004;Ida et al, 2005;Ida and Hayakawa, 2006;Kotsarenko et al, 2004Kotsarenko et al, , 2005Kotsarenko et al, , 2007, principal component analysis (Gotoh et al, 2002;Hattori et al, 2004;Kotsarenko et al, 2005), and singular value decomposition , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a key issue of a study of ULF anomalies is to discriminate signals related to EQs from signals of other origin. Different methods have been proposed to solve this problem, such as the polarization analysis of EM waves (Kawate et al, 1998;Kotsarenko et al, 2004Kotsarenko et al, , 2005Hayakawa et al, 2008); fractal and multi-fractal analysis (Hayakawa et al, 1999;Gotoh et al, 2003;Smirnova et al, 2004;Kotsarenko et al, 2004Kotsarenko et al, , 2005Kotsarenko et al, , 2007; the Principal Component Analysis (PCA) Kotsarenko et al, 2005); location of the area of seismogenic geomagnetic disturbances Kopytenko et al, 2001); and signal/noise discrimination by using the transfer functions , among others. All the abovementioned methods are applied to improve the detection of the ULF signals associated with seismogenic phenomena at different frequencies , and to the understanding of electromagnetic phenomena associated with tectonic and volcanic activity.…”
Section: Introductionmentioning
confidence: 99%